SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PEMILIHAN DOSEN PEMBIMBING SKRIPSI FAKULTAS ILMU KOMPUTER UNIVERSITAS AL WASHLIYAH (UNIVA) LABUHANBATU BERDASARKAN MINAT MAHASISWA DENGAN METODE AHP - Sahbudin Ritonga, Desi Deliyanti Ritonga; Subagio, S; Aditya, Rahmad (LPPM Universitas Al Washliyah Labuhanbatu, 2024)
Determination of the thesis supervisor at the Faculty of Computer science, Al Washliyah University (UNIVA) Labuhanbtu is currently carried out by determining directly by determining the thesis supervisor to direct and assist in completing the thesis. The main objective of this research is to determine the thesis supervisor of the Faculty Computer science, University of Al Washliyah (UNIVA) Labuhanbatu, the method used in determining the supervisor is using the AHP (Analytical Hierarchy Process) method. The creation of this system begins. Observing and searching for data, analyzing and collecting data, designing, programming, and the application uses the visual basic programming language, source code and access database for its database. The final result of this research is to produce a decision support system for determining thesis supervisor using the AHP (Analytical Hierarchy Process) method.